Prevalence and cumulative incidence of abnormal cervical cytology among HIV-infected Thai women: A 5.5-year retrospective cohort study - Amphan Chalermchockcharoenkit (2018)
Background: Cervical cancer is one of the most common AIDS-related malignancies in Thailand. To prevent cervical cancer, The US Public Health Service and The Infectious Disease Society of America have recommended that all HIV-infected women should obtain 2 Pap smears 6 months apart after the initial HIV diagnosis and, if results of both are normal, should undergo annual cytological screening. However, there has been no evidence in supporting whether this guideline is appropriate in all settings - especially in areas where HIV-infected women are living in resource-constrained condition.Methods: To determine the appropriate interval of Pap smear screenings for HIV-infected Thai women and risk factors for subsequent abnormal cervical cytology, we assessed the prevalence, cumulative incidence and associated factors of cervical cell abnormalities (atypical squamous cell of undetermined significance or higher grades, ASCUS+) among this group of patients.Results: The prevalence of ASCUS+ was 15.4% at the first visit, and the cumulative incidence of ASCUS+ gradually increased to 37% in the first 3.5 years of follow-up appointments (first 7 times), and tended to plateau in the last 2 years. For multivariate correlation analysis, women with a CD4 count < 350 cells/μL had a significant correlation with ASCUS+ (P = 0.043). There were no associations of subsequent ASCUS+ with age, pregnancy, contraceptive method, highly active anti-retroviral treatment, assumed duration of infection, or the CD4 count nadir level.Conclusion: There are high prevalence and cumulative incidence of ASCUS+ in HIV-infected Thai women. With a high lost-to-follow-up rate, an appropriate interval of Pap smear screening cannot be concluded from the present study. Nevertheless, the HIV-infected Thai women may require more than two normal semi-annual Pap smears before shifting to routinely annual cytologic screening. © 2011 Chalermchockcharoenkit et al; licensee BioMed Central Ltd.